INTEREST RATES IN INDONESIAN BANKS' ASYMMETRIC BEHAVIOR AND DEGREE OF PASSTHROUGH - Tohap Parulian; A. Mahendra; Witya Shalini (RADJA PUBLIKA, 2023)
Interest rate changes result in a trade-off between reducing inflation and capital inflows. Capital inflow will reduce money market interest rates as low as possible, followed by lower lending and deposit rates. On the other hand, it is difficult to lower the benchmark interest rate due to inflation pressure. The asymmetric movement of lending and deposit interest rates to the benchmark interest rate has caused disturbances to the monetary transmission mechanism. The results of the estimated error-correction model for variable lending rates found that the long-term passthrough of Indonesian banks was significant but could have been better on interest rates on working capital loans and investment loans. This study shows an asymmetrical behavior in banking interest rates in Indonesia. The passthrough degree is typically slow when there is a decrease in the benchmark interest rate.